สภาพ ปัญหาและแนวทางการบริหารหลักสูตรอิสลามศึกษาแบบเข้ม ในโรงเรียนของรัฐ จังหวัดสงขลา - ทอดทิ้ง พิชยา; ยี่สุ่นทรง อะห์มัด (Al-HIKMAH Journal, 2018)
This research aimed to examine and compare states, problems of intensive Islamic studies curriculum administration in the public schools, Songkhla Province and to propose guidelines of Intensive Islamic studies curriculum administration in the Schools. The key informants included 12 informants of interview data and 155 informants of quantitative data consisting of administrators, heads of academic administration unit and intensive Islamic studies teachers. A mixed method research design which based on exploratory design for developing instrument was used in this research. The statistics employed to analyze the data consists of percentage, average, standard deviation, T (t-test) and F (F-test) and content analysis for qualitative data.The findings of this studies were as follows: the overall level of states, problems of intensive Islamic studies curriculum administration in the public schools, Songkhla Province is high in all dimensions. The results of the comparison of states, problems of intensive Islamic studies curriculum administration of administrators, heads of academic administration nit and intensive Islamic studies teachers in the Schools based on sex, work positions, age showed that there were no significant differences between groups with respect to this demographic data. However, the level of problems of intensive Islamic studies curriculum administration was found to have a statistically significant difference between group with respect to educational qualification and work experiences at 0.05. The proposed suggestions and guidelines of intensive Islamic studies curriculum administration in the public schools, Songkhla Province are 1) on the preparation for curriculum administration. 2) On the curriculum implementation plan. 3) On the curriculum administration operation (the curriculum implementation). 4) On the supervision, monitoring, follow-up and internal evaluation